1983
DOI: 10.1111/j.1365-2621.1983.tb10744.x
|View full text |Cite
|
Sign up to set email alerts
|

High Vacuum Flame Sterilization of Canned Diced Tuna: Preliminary Process Development and Quality Evaluation

Abstract: A preliminary study of the potential of high vacuum flame sterilizing canned diced tuna was carried out. The investigation included inoculated experimental sighting packs study at five process levels, and comparative assessment of the physical, chemical and nutritional property of the raw, precooked, high vacuum flame sterilized (HVFS) and still-retorted canned tuna. The vacuum achieved in the HVFS packs was significantly higher (P < 0.05) than the control packs. Fatty acid and amino acid composition, in-vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Extensive research has been reported on the various aspects of thermal-processed tuna. Nutritive value of canned foods (Kramer, 1946), changes in protein quality and lysine upon canning (Banga et al, 1992;Castrillon et al, 1996), postmortem stress on the quality of canned tuna (Crawford et al, 1970) and various quality attributes of canned tuna are reported (Duane Brown & Tappel, 1957;Ali Khayat, 1977;Seet et al, 1983;Shim et al, 2004;Jeyashakila et al, 2005). Effect of packing media like extra virgin olive oil on the oxidation of canned tuna lipids are reported (Medina et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been reported on the various aspects of thermal-processed tuna. Nutritive value of canned foods (Kramer, 1946), changes in protein quality and lysine upon canning (Banga et al, 1992;Castrillon et al, 1996), postmortem stress on the quality of canned tuna (Crawford et al, 1970) and various quality attributes of canned tuna are reported (Duane Brown & Tappel, 1957;Ali Khayat, 1977;Seet et al, 1983;Shim et al, 2004;Jeyashakila et al, 2005). Effect of packing media like extra virgin olive oil on the oxidation of canned tuna lipids are reported (Medina et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…(Hell, 1983) HTST with still retort contin agitation sterilizing value (F12i.i=c10°c), min thermal degradation value (C12U=c26°c), min retention of thiamin (AOAC, 1975), % 25 123 16.0 ± 2.0 33 39 55.8 ± 14.8 Table II. Consequences of Thermal Processes for Canned Whole Peeled Tomatoes (Leonard et al, 1975a,b) and the actual percent retentions of thiamin (Seet et al, 1983). One of the processes involved cooking the canned product 120 min at 115.6 °C in a still retort; the other employed a high-temperature/short-time (HTST) sterilization procedure with continuous agitation (Heil, 1983).…”
Section: Products (I) Heat-labile Constituent Heat-stable Substancesmentioning
confidence: 99%
“…RECENT WORK on high vacuum flame sterilization (HVFS) has demonstrated the potential for this low liquid process to improve product quality (Carroad et al, 1980;Leonard et al, 1983Leonard et al, , 1984aO'Mahony et al, 1983;Schweingruber et al, 1981;Seet et al, 1983). Among the products which were successfully high vacuum flame sterilized , green beans with enclosed pockets of gas, and apples with their gas-laden, heat-sensitive tissues were particularly difficult to deaerate using a pilot HVFS processing system with flame deaeration, followed by flame sterilization for low acid foods.…”
Section: Introductionmentioning
confidence: 99%